2011
DOI: 10.1038/nchembio.628
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic evidence for a front-side, SNi-type reaction in a retaining glycosyltransferase

Abstract: 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
189
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(209 citation statements)
references
References 55 publications
20
189
0
Order By: Relevance
“…The structure showed that hydrogen bonding existed between the leaving group oxygen of UDP and the nucleophile mimic of the sugar moiety, suggestive of an S N i-like reaction mechanism. Kinetic isotope effects and linear free energy relationship experiments (40), along with computational studies (41) on the inhibitor complex, confirmed that VA6P and UDP acted together as synergistic transition state mimics, supporting front-face nucleophilic attack involving hydrogen bonding between leaving group and nucleophile. Structural comparison with our TarM ternary-like complex reveals a very similar active site composition with good structural agreement between UDP and donor sugar glycoside products (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…The structure showed that hydrogen bonding existed between the leaving group oxygen of UDP and the nucleophile mimic of the sugar moiety, suggestive of an S N i-like reaction mechanism. Kinetic isotope effects and linear free energy relationship experiments (40), along with computational studies (41) on the inhibitor complex, confirmed that VA6P and UDP acted together as synergistic transition state mimics, supporting front-face nucleophilic attack involving hydrogen bonding between leaving group and nucleophile. Structural comparison with our TarM ternary-like complex reveals a very similar active site composition with good structural agreement between UDP and donor sugar glycoside products (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Recently, it was reported that relatively high values for -SD(T)KIEs were observed in the synthesis reaction of ,-trehalose 6-phosphate by ,-trehalose 6-phosphat synthase (UDP forming) as a retaining glycosyltransferase (EC 2.4.1.15): the values forand -SDKIEs are 1.20 and 1.16, respectively, and the value for -STKIEs, 1.16. 38,39) This implies that, in the enzyme classified into the category of transferase (EC 2 groups) too, the splitting reaction of the C 1 -O bond of UDPglucose occurs through resonance between oxocarbenium ion and the carbocation intermediate.…”
Section: )mentioning
confidence: 99%
“…Recently, in a detailed exhaustive study (15), the reaction catalyzed by OtsA has been shown to proceed through a highly dissociative oxocarbenium ion-like transition state, with a substantial participation of the incoming nucleophile through hydrogen bonding donation to the leaving group. This finding and the demonstration that the OtsA/UDP/validoxamine A 6 0 -Ophosphate represents a transition state mimics have been interpreted as a mechanistic evidence of a front-side S N i-like reaction mechanism (Path A, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4), as long as the hydrogen bonding interaction between the donor and acceptor molecules is preserved. In particular, the KIE (KIE 5 1.164) observed when the hydrogen atom attached to the C2 of the glucosyl moiety of the donor was substituted by a deuterium was interpreted as a large b-secondary effect, which highlighted the hyperconjugation of the C2À ÀH r-bond and the electron-deficient C1 carbon of the oxocarbenium (15). The difference between extensive hyperconjugation and full donation of the C2À ÀH r-bond electrons is subtle, and the formation of a C1-C2 double bond could be viewed as an extreme case of hyperconjugation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation